A Pattern Language for the Teaching and Practice of Technology Management - Fortino, Andres (Senate Hall Academic Publishing, 2006)
The work of architect Christopher Alexander in articulating the field of pattern languages for architecture has been extended to several other fields, notably object oriented software development and project management. Alexander calls for the identification of patterns in areas of creativity (e.g. architecture, programming) and of human activity (e.g. project management) which when taken together form a comprehensive and interrelated set of entities comprising a language that defines best practices in that area. Alexander has identified a well-defined process to identify patterns and criteria for selecting and creating patterns beneficial for action by the practitioner. Most often the discovery of patterns and development of a language for a field of practice is carried out by a community of practitioners. This paper presents the application of Alexander’s pattern language approach to teaching technology management practice. Specifically it proposes the development of a community of technology managers, practitioners and educators to discover patterns and create a pattern language for technology management. Examples of patterns in technology management and their derivation from industry laws (such as Moore’s Law) are presented as a staring point in the discussion.
Keywords: patterns; pattern language; best practices; teaching; IT laws; community of practice